Recovery in mental health: a formative construction for psychiatric nursing - Higino da Silva, Luciana Silvério Alleluia (2020)
Objective: To understand nursing care based on recovery practices in a psychiatric hospital. hospitalized. Qualitative study method with a sociopoetic approach. The data were produced in two meetings with hospitalized people, through participant observation. The group consisted of eight people. The data analyzed and divided into three categories: Institutional Care, Institutional Care and Internal Care-Action. Discussion / Results: Based on the categories found, the discussion was based on reflections anchored in Foucault, Goffman and Lourau. The study revealed that hospitalized people look for resources to deal with the daily routine of hospitals, as they are crossed by power and hierarchy relationships; report that it is necessary to establish links between them and the professionals, finally they believe that trust must be mutual. Conclusion: There is a need for productions where hospitalized people are protagonists of the actions. He understands that nursing care needs to encompass psychosocial dimensions in order to build a unique care of strategies to deal with the hospitalized person, which it confers as good care practices.